2000
DOI: 10.1212/wnl.55.2.281
|View full text |Cite
|
Sign up to set email alerts
|

Hallucinations, REM sleep, and Parkinson’s disease

Abstract: The visual hallucinations that coincide with daytime episodes of REM sleep in patients who also experience post-REM delusions at night may be dream imagery. Psychosis in patients with PD may therefore reflect a narcolepsy-like REM sleep disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
233
4
14

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 410 publications
(259 citation statements)
references
References 33 publications
8
233
4
14
Order By: Relevance
“…Sleep disturbance, which is characterized by excessive daytime sleepiness with frequent naps, often occurs in PD patients [6] . However, the etiology of these symptoms remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep disturbance, which is characterized by excessive daytime sleepiness with frequent naps, often occurs in PD patients [6] . However, the etiology of these symptoms remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…All of these symptoms are reminiscent of human narcolepsy, a sleep disorder caused by the dysfunction of orexin neurons [6] . Furthermore, many postmortem morphological studies in the function of orexin system have revealed a decreased level of orexin in CSF and reduced number of orexin neurons in PD patients [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…The combination of targeted questions probing visual misperceptions with questions interrogating related symptomology, such as sleep disturbance [11,34] and attention network dysfunction [16], will allow for the prospective assessment of concomitant patterns of dysfunction associated with VH. Indeed, the results of our analysis suggest that there is a strong correlation between self-reported visual misperceptions (Q [1][2][3][4][5][6] ) and all other symptomatic categories assessed.…”
Section: Discussionmentioning
confidence: 99%
“…However, the nonresponder cohort was significantly older (mean age: 72. 6 ; n = 76); sensory misperceptions (Q 7-10 ; n = 45); and disordered thought (Q [11][12][13] ; n = 17). 15 Impaired multitasking 121 61 Q 16 Following conversation 93 47 Q 17 Day dreaming 95 48 Q 18 Vivid dreams 129 65 Q 19 REM behavior disorder 89 45 Q 20 Confusion upon waking 46 23…”
Section: Psych-q Responsesmentioning
confidence: 99%
“…The presence in PD patients of narcolepsy-like features, such as daytime REM sleep intrusions associated with visual hallucinations, has led some authors to suggest that a mechanism similar to that of narcolepsy might underlie excessive daytime sleepiness (EDS) in PD (Arnulf et al, 2000). Thannickal et al (2007) demonstrated that a massive loss of orexin neurons was found in PD patients and suggested that it was a cause of the narcolepsy-like symptoms.…”
Section: Narcolepsy-like Symptomsmentioning
confidence: 99%